2013
DOI: 10.1007/s10456-013-9343-z
|View full text |Cite
|
Sign up to set email alerts
|

TR-644 a novel potent tubulin binding agent induces impairment of endothelial cells function and inhibits angiogenesis

Abstract: TR-644 is a novel combretastatin A-4 (CA-4) analogue endowed with potent microtubule depolymerizing activity superior to that of the lead compound and it also has high affinity to colchicines binding site of tubulin. We tested TR-644 anti-angiogenic effects in human umbilical endothelial cells (HUVEC). It showed no significant effects on the growth of HUVEC cells at concentrations below 1,000 nM, but at much lower concentrations (10-100 nM) it induced inhibition of capillary tube formation, inhibition of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 45 publications
6
42
0
Order By: Relevance
“…Compared with HUVEC, MMEC expressed a higher level of livin and cdc25A and a lower level of p21. This is in line with previous reports indicating that downregulation of cdc25 and upregulation of p21 expression in EC correlates with cell cycle arrest [25, 26]. With regard to livin, an inhibitor of apoptosis proteins, our observations show that its expression is positively correlated with cell survival [27].…”
Section: Discussionsupporting
confidence: 82%
“…Compared with HUVEC, MMEC expressed a higher level of livin and cdc25A and a lower level of p21. This is in line with previous reports indicating that downregulation of cdc25 and upregulation of p21 expression in EC correlates with cell cycle arrest [25, 26]. With regard to livin, an inhibitor of apoptosis proteins, our observations show that its expression is positively correlated with cell survival [27].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, in this study, CA-4P inhibited sprout formation at concentrations that did not inhibit the proliferation of endothelial cells, confirming direct antiangiogenic properties of CA-4P. Similarly, modulation of endothelial cells by combretastatin analogs has been reported in vitro (Dupeyre et al, 2006;Kong et al, 2010;Romagnoli et al, 2010;Sanna et al, 2010;Arthuis et al, 2011;Porcù et al, 2013) and in vivo (Fortin et al, 2011;Porcù et al, 2013;Zheng et al, 2014). The molecular mechanism of the antiangiogenic properties of TR-644 CA-4 analog was linked to the inhibition of vascular endothelial growth factor-induced phosphorylation of VE-cadherin (Porcù et al, 2013).…”
Section: Inhibitors Of Neovascularization/angiogenesissupporting
confidence: 78%
“…Similarly, modulation of endothelial cells by combretastatin analogs has been reported in vitro (Dupeyre et al, 2006;Kong et al, 2010;Romagnoli et al, 2010;Sanna et al, 2010;Arthuis et al, 2011;Porcù et al, 2013) and in vivo (Fortin et al, 2011;Porcù et al, 2013;Zheng et al, 2014). The molecular mechanism of the antiangiogenic properties of TR-644 CA-4 analog was linked to the inhibition of vascular endothelial growth factor-induced phosphorylation of VE-cadherin (Porcù et al, 2013). It has also been suggested that CA-4 may exert its antiangiogenic properties by downregulation of connective tissue growth factor, a negative regulator of angiogenesis (Samarin et al, 2009).…”
Section: Inhibitors Of Neovascularization/angiogenesismentioning
confidence: 92%
See 1 more Smart Citation
“…162 Other combretastatin-like compounds also inhibited cell migration and/or metastasis. 149,167,168 In particular, compound 12 reduced lymph node metastasis of LY80 Yoshida sarcoma in mice by shutting down the blood flow even in small metastases. These observations suggest that combretastatin-mediated vascular shutdown not only affects large primary tumors but also micrometastases.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%